EVALUATING THE INFLUENCE OF KFC ON CONSUMERS FOOD WASTE MANAGEMENT AWARENESS & BEHAVIOURS: WHAT’S THE TAKEOUT? - Luthuli, Nikiwe (The IIE, 2021)
With the Quick Service Restaurant industry growing within the South African context and demand for fast food options increasing, food waste in the home is at an all-time high while food waste management within homes is at an all time low. The dominant explanation for this is that the more fast-food and takeaways consumers have access to the greater the risk for food in the home to be eligible for waste. Previous research reports have shown that the main reason people at consumer level account for 5 – 10% of food waste is the lack of clear information on food waste management. Research that explains the effect that the QSR industry has on food waste management in the household is limited, more so within the South African context. To gain more insight into this topic, the research study performed a quantitative investigation of the influence that specifically KFC as a brand has on its consumers’ mindsets and behaviours towards food waste management at a buying and consumption level. The results show that there is no direct correlation between KFC and food waste management but that indirectly the QSR industry plays a role in increasing the prevalence of food waste in the home. From a future-forward perspective, this correlation emphasizes the need for the QSR industry, specifically KFC, to educate their consumers on food waste and the management thereof.
Keywords: Meaningful brands; Quick Service Restaurant industry; Consumer education; Customer behaviour